Promoting The Usage of Business Model Canvas for Tourism Development in Sugihmukti Village, Bandung Regency - Aisha Nur Izzati; Irni Yunita; Fajar Sidiq Adi Prabowo (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Based on Decree No. 556/Kep.770-Disbudpar/2022, issued in 2002, Sugihmukti Village in Bandung Regency was officially designated as a tourism village. Sugihmukti Village is known for its birdwatching activities conducted in collaboration with